How to Modify Habitat to Discourage Nuisance Wildlife in Your Yard - Holly K. Ober; Arlo Kane (EDIS)
Although often overlooked, habitat modification is the cheapest and most effective long-term solution to nuisance wildlife problems in residential landscapes. Removing the resources wildlife are seeking when they visit your yard can be a much more cost-effective solution than restricting access to those resources with physical barriers, scaring wildlife with hazing tactics, deterring wildlife with repellents, or removing wildlife by trapping or killing nuisance animals. This 3-page fact sheet was written by Holly K. Ober and Arlo Kane, and published by the UF Department of Wildlife Ecology and Conservation, October 2012.